Citizen science reveals complex changes in barn swallow phenology in South Africa over three decades - Burman, Marc Sebastian (Department of Biological Sciences, 2017)
Palearctic migrants, including barn swallows Hirundo rustica, responded to climate change in Europe from the mid to late 1900s with phenological changes, mostly showing earlier arrival and start of breeding. During this period, barn swallows in the Palearctic exhibited variable patterns of change in the timing of their arrival, breeding and departure from the breeding grounds. At the South African non-breeding grounds, the timing of migration shifted between the 1980s and 2000s, again with geographic variability. To explain these changes further, I examined geographic and temporal variability in the timing of flight feather ('primary') moult, and trends in body weight, in barn swallows ringed in South Africa between 1986 and 2012. Citizen science bird ringing, started in South Africa in 1948, generated all the data used in this project. All data were obtained from the South African Bird Ringing Unit (SAFRING).